ANALYZING SPENCER 2021 MOVIE: HOW DO WE MAKE REFUSAL STRATEGIES? - Hanifatul Wahda; Afiifah Al Rosyiidah (HISKI, 2022)
This study uses the movie of Spencer 2021 to describe the types of refusal strategies and the sequences of refusal strategies. This study uses a descriptive qualitative method. The results show that there are 2 types of refusal strategies:direct refusal and indirect refusal strategies. There are several subtypes included in the classification: reasons or explanations (12 data), attempts to obstruct the interlocutor (6 data) statements of principle (4 data), non-performative statements (5 data), statements of regret (3 data), alternative statements (2 data), acceptance that functions as a refusal (1 data) and avoidance (1 data). In addition, the sequences of refusal strategies consist of post refusal (22 data), pre-refusal (15 data) and main refusal (6 data). AbstrakPenelitian ini menggunakan film Spencer 2021 untuk mendeskripsikan jenis-jenis strategi penolakan dan urutan strategi penolakan. Penelitian ini menggunakan metode kualitatif deskriptif. Hasil penelitian menunjukkan bahwa terdapat 2 jenis strategi penolakan: strategi penolakan langsung dan strategi penolakan tidak langsung. Terdapat beberapa subtipe yang termasuk dalam klasifikasi tersebut: alasan atau penjelasan (12 data), upaya menghalangi lawan bicara (6 data) pernyataan prinsip (4 data), pernyataan non-performatif (5 data), pernyataan penyesalan (3 data), pernyataan alternatif (2 data), penerimaan yang berfungsi sebagai penolakan (1 data) dan penghindaran (1 data). Selain itu, urutan strategi penolakan adalah post refusal (22 data), pre-refusal (15 data) dan main refusal (6 data).